Evidence of different feeding rates within an anchovy shoal - C Robinson; V Arenas (Ciencias Marinas, 1995)
A single shoal of northern anchovy (Engraulis mordax) was captured and sampled in Baja California, Mexico. The fish were sized, weighed and the first branchial arch of the left side was used for counting the number of gill rakers. The stomach content was weighed and the number of microplankters recorded. It was found that the weight of the stomach content increases with fish length as well as the number of microplankters. However, the number of microplankters per gram of fish and stomach content weight decreases with fish length. The number of gill rakers does not increase with fish length. The results follow a similar pattern to that observed using equations obtained from previous laboratory studies. It is suggested that within a shoal of anchovies, composed of differently sized individuals, different rates of feeding may exist.